THE ROLE OF THE LAW IN THE PROTECTION OF RARE AND ENDANGERED PLANT SPECIES IN UZBEKISTAN - Babomirzaev Moumunjan Ergashovich (Next Scientists Conferences, 2023)
The article "The role of the law in the protection of rare and endangered plant species in Uzbekistan" examines the impact of legal mechanisms on the conservation of biodiversity in the context of the threat of extinction of rare plant species. The authors analyze the legislative acts of Uzbekistan aimed at regulating the use of natural resources and environmental protection. The article examines the effectiveness of existing laws, their compliance with international standards in the field of nature protection, and also offers recommendations for improving the legislative framework in order to more effectively protect rare and threatened plant species. The results of the study emphasize the importance of a balanced approach to legislation that takes into account the needs of society and the requirements of environmental policy to achieve sustainable human interaction with nature.